Epidemiological characteristics and disease burden of childhood neuroblastoma in Asia: trends and regional differences over the past 30 years - Li, Zexi; Liu, Jing; Wu, Yurui (Frontiers in Pediatrics, 2025)
BackgroundNeuroblastoma (NB) is the most common extracranial solid tumor in children, with significant clinical heterogeneity. Despite Asia's large pediatric population, comprehensive studies on its disease burden remain limited.ObjectiveThis study aims to evaluate trends in NB disease burden among Asian children (0–14 years) from 1990 to 2021, examining age, sex, and socioeconomic variations.MethodsUsing Global Burden of Disease (GBD 2021) data, we analyzed incidence, prevalence, deaths, and disability-adjusted life years (DALYs). Statistical analysis was performed using R (v4.5.0), with stratification by Socio-Demographic Index (SDI), age, and sex. Spatial distribution and annual percentage changes were visualized using ggplot2 and heatmaps.ResultsFrom 1990 to 2021, NB burden increased significantly across Asia. Males showed higher burden than females, with infants (1–11 months) at greatest risk. East Asia experienced the fastest growth, while South Asia had the highest absolute burden. High-SDI regions demonstrated declining trends of disease burden but maintained the highest case numbers. Country-level variations were substantial, with Qatar and Afghanistan showing the largest increases and Kyrgyzstan the greatest reductions. SDI correlated positively with NB burden, suggesting improved detection in developed regions. Females exhibited bimodal incidence peaks (6–11 months and 5–9 years), while males peaked at 1–5 months and 2–4 years.ConclusionThe burden of NB in Asian children is characterized by age and gender differences and socioeconomic drivers. It is necessary to optimize screening and resource allocation strategies for high-risk groups.